2020
DOI: 10.1136/jmedgenet-2019-106678
|View full text |Cite
|
Sign up to set email alerts
|

Severity of oro-dental anomalies in Loeys-Dietz syndrome segregates by gene mutation

Abstract: Background Loeys-Dietz syndrome (LDS), an autosomal dominant rare connective tissue disorder, has multisystemic manifestations, characterised by vascular tortuosity, aneurysms and craniofacial manifestations. Based on the associated gene mutations along the transforming growth factor-beta (TGF-β) pathway, LDS is presently classified into six subtypes. Methods We present the oro-dental features of a cohort of 40 patients with LDS from five subtypes. Results The most common oro-dental manifestations were the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…We previously reported the oral manifestations in a cohort of 40 individuals with LDS from five subtypes (LDS1-5) and reported a high frequency of abnormal palate morphology, enamel defects, bifid uvula, or submucous cleft palate, malocclusion, dental crowding, and delayed eruption of permanent teeth (16). We concluded that individuals with LDS2 followed by LDS1 had the most severely affected oro-dental region, which is also true for the systemic manifestations reported in LDS literature.…”
Section: Introductionsupporting
confidence: 53%
“…We previously reported the oral manifestations in a cohort of 40 individuals with LDS from five subtypes (LDS1-5) and reported a high frequency of abnormal palate morphology, enamel defects, bifid uvula, or submucous cleft palate, malocclusion, dental crowding, and delayed eruption of permanent teeth (16). We concluded that individuals with LDS2 followed by LDS1 had the most severely affected oro-dental region, which is also true for the systemic manifestations reported in LDS literature.…”
Section: Introductionsupporting
confidence: 53%
“…Further investigations into TGFβ abrogation later in skeletal development could provide information relevant to skeletal diseases initiated later in life. Based on our mouse skeletal phenotype, we suggest that our CKO mice may provide a good model to investigate how TGFβ signaling contributes to the craniosynostosis and oro-dental anomalies demonstrated in Loeys-Dietz syndrome [ 44 , 48 , 49 , 50 , 51 , 52 ]. Future investigations should include in-depth static and kinetic morphometric analysis building upon our previous publication demonstrating rigorous quantification of histomorphometric changes in the CKO long bones, growth plates, and calvaria [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of enamel defects was graded using a classification system for enamel defects reported previously (Jani et al, 2020). The classification of dental enamel defects was applied for both deciduous and permanent dentitions.…”
Section: Methodsmentioning
confidence: 99%